Rancang Bangun Acwh Dengan Model Tanki Horizontal Dan Penambahan Pcm Sebagai Isolator Dari Sumber Panas - Rosadi, Irham; Siregar, Chandra Amirsyahputra; Siregar, Ahmad Marabdi; Lubis, Riadini Wanty; Fadillah, Fahri; M, Moranelo (Rekayasa Material, Manufaktur dan Energi, 2022)
Into several stages, namely design, material selection and manufacture. The design uses solidworks 2013 software which includes frame design, tank design, Helical-Coil heat exchanger design and the stage of uniting components designed to be able to flow refrigerant heat to water. The stage of making the tool follows from the design that has been made, namely the frame using angle iron (L) with dimensions of 750mm x 390mm x 1500mm, the tank uses a stainless steel plate and the addition of PCM around the tank with a capacity of 60 liters and an overhaul of the compressor outlet flow that is routed to the Helical-Coil heat exchanger made of copper with a diameter of 6.35mm with APK dimensions 150mm x 300mm or half of the tank height. From the test results, ACWH can work well as evidenced by not using PCM, increasing water temperature with the addition of PCM reaching 60.25 oC within 7 hours of testing, while not using PCM water temperature reaching 60.17 oC within 10 hours.